A Library Sets Sail (Res Medica, 2014)
Hurry down New Bond Street too fast and miss the main entrance of the Sotheby salerooms.  It is a small fronting done out in fading cream paint with the apologetic air of a second rate bookie’s office.  But inside the building expands into a veritable Ali Baba’s cave for there is no denying the pivotal position of Sotheby & Co. in the world of fine art, of books, of the rare and the beautiful.  The front entrance is, by some quirk, no more than a curious self-effacement in the centre of exhibitionist London, and the eighteenth Egyptian dynasty animal statue (circa 1320 BC) perched above the twin doorways and entitled SEKHMET appears to be having the last laugh.